Degradation of the Organochlorinated Herbicide Diuron by Rainforest Basidiomycetes - Henn, Caroline; Arakaki, Ricardo M. [UNESP]; Monteiro, Diego Alves [UNESP]; Boscolo, Mauricio [UNESP]; Silva, Roberto da [UNESP]; Gomes, Eleni [UNESP] (Hindawi Ltd, 2020)
The main organochlorinated compounds used on agricultural crops are often recalcitrant, affecting nontarget organisms and contaminating rivers or groundwater. Diuron (N-(3,4-dichlorophenyl)-N ',N '-dimethylurea) is a chlorinated herbicide widely used in sugarcane plantations. Here, we evaluated the ability of 13 basidiomycete strains of growing in a contaminated culture medium and degrading the xenobiotic. Dissipation rates in culture medium with initial 25 mg/L of diuron ranged from 7.3 to 96.8%, beingPluteus cubensisSXS 320 the most efficient strain, leaving no detectable residues after diuron metabolism.Pycnoporus sanguineusMCA 16 removed 56% of diuron after 40 days of cultivation, producing three metabolites more polar than parental herbicide, two of them identified as being DCPU and DCPMU. Despite of the strong inductive effect of diuron upon laccase synthesis and secretion, the application of crude enzymatic extracts ofP. sanguineusdid not catalyzed the breakdown of the herbicide in vitro, indicating that diuron biodegradation was not related to this oxidative enzyme.